2021
DOI: 10.1093/nar/gkab812
|View full text |Cite
|
Sign up to set email alerts
|

High resolution copy number inference in cancer using short-molecule nanopore sequencing

Abstract: Genome copy number is an important source of genetic variation in health and disease. In cancer, Copy Number Alterations (CNAs) can be inferred from short-read sequencing data, enabling genomics-based precision oncology. Emerging Nanopore sequencing technologies offer the potential for broader clinical utility, for example in smaller hospitals, due to lower instrument cost, higher portability, and ease of use. Nonetheless, Nanopore sequencing devices are limited in the number of retrievable sequencing reads/mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…However, there have been several studies to take advantage of long-read sequencing instruments in sequencing shorter molecules. Some assays [OCEAN, MAS-Iso-Seq] work by either concatenating (8, 28) or otherwise preparing(29) short molecules for sequencing on the PacBio or ONT instrument. While these assays can generate more short reads, they either have to contend with the high cost of the PacBio Sequel IIe sequencer, or the low per-base accuracy of raw ONT reads which even with the latest guppy5 algorithm is only 96% in our hands.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been several studies to take advantage of long-read sequencing instruments in sequencing shorter molecules. Some assays [OCEAN, MAS-Iso-Seq] work by either concatenating (8, 28) or otherwise preparing(29) short molecules for sequencing on the PacBio or ONT instrument. While these assays can generate more short reads, they either have to contend with the high cost of the PacBio Sequel IIe sequencer, or the low per-base accuracy of raw ONT reads which even with the latest guppy5 algorithm is only 96% in our hands.…”
Section: Discussionmentioning
confidence: 99%
“…ichorCNA analysis. Samtools (Version 1.9) was used to filter BAM alignments, unmapped reads, secondary and supplementary reads, reads with mapping quality less than 20 as in (44), and reads longer than 700bp. For Illumina alignments we trimmed all 'N' nucleotides from the 3' ends of fastq data, alignments were performed to GCF_000001405.39_GRCh38.p13 with BWA mem (43), duplicates were marked using picard MarkDuplicates and removed with samtools;read pairs without the properly-paired flag were removed.Pipelines used for preprocessing and filtering of both Nanopore and Illumina data are available at https://github.com/Puputnik/Fragmentomics_GenomBiol.…”
Section: Methodsmentioning
confidence: 99%
“…ONT has primarily been used for long-read sequencing, but recent work by our group and others has shown that it can be adapted for short fragments without additional processing steps (16)(17)(18). As an added benefit, the ability to capture much longer cfDNA fragments than shortread sequencing may lead to new discoveries or biomarkers, as was demonstrated recently in the case of longer fragments during pregnancy (19).…”
Section: Introductionmentioning
confidence: 99%
“…Given that this type of variant impacts the greatest number of nucleotides in a genome, it is not surprising that evidence is mounting regarding their importance across all categories of life. This starts e.g., with important speciation events 3 and impacts plants 4,5 , but goes further across human diseases (Mendelian 6,7 as well as complex diseases [8][9][10] ) to cancer development [11][12][13] (e.g., HLA loss, oncogene amplification). Despite the importance of SVs, we are still struggling to detect germline vs. somatic SVs or even robustly identify de novo SVs [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%